2020
DOI: 10.1038/s41598-020-58994-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for the development of proteinuria in cancer patients treated with bevacizumab, ramucirumab, and aflibercept: a single-institution retrospective analysis

Abstract: The development of proteinuria restricts the dose of anti-angiogenic agents, thereby reducing their efficacy. Thus, this retrospective study was undertaken to identify predictive factors of the development of angiogenesis inhibitor-induced proteinuria, and to elucidate if there is a difference in the likelihood of proteinuria among anti-angiogenic agents or cancer types, to help guide future strategies to improve the safety, efficacy, and quality of life of patients receiving chemotherapy. Between April 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
(11 reference statements)
2
23
2
1
Order By: Relevance
“…The predictive factors for the development of proteinuria in patients receiving anti-VEGF therapy were identified as high systemic blood pressure, calcium channel blocker administration, and a higher number of therapy cycles [ 14 ]. Our patient had used a calcium channel blocker, but his systolic blood pressure remained high.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive factors for the development of proteinuria in patients receiving anti-VEGF therapy were identified as high systemic blood pressure, calcium channel blocker administration, and a higher number of therapy cycles [ 14 ]. Our patient had used a calcium channel blocker, but his systolic blood pressure remained high.…”
Section: Discussionmentioning
confidence: 99%
“…The increased loss of proteins in urine (proteinuria) represents a common event in cancer patients treated with angiogenesis inhibitors, though its incidence may be vary from study to study. Significant predictors for the development of proteinuria may include the number of cycles (>13), the systolic blood pressure at baseline ≥ 135 mmHg, and the use of calcium channel blockers [ 20 ]. Systemic hypertension is a postulated pathogenic mechanism in the development of such proteinuria, through an increase in intraglomerular pressure [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, the combination of paclitaxel with ramucirumab in patients with gastric cancer was not identified as a risk factor for proteinuria. It has been reported that the total dose of bevacizumab is a risk factor for proteinuria (6,13). The target drugs evaluated by Kanbayashi et al (13) were bevacizumab, ramucirumab and aflibercept, which may be a factor contributing to this observation.…”
Section: Number Of Patients With Proteinuria N (%) -mentioning
confidence: 97%
“…It has been reported that the total dose of bevacizumab is a risk factor for proteinuria (6,13). The target drugs evaluated by Kanbayashi et al (13) were bevacizumab, ramucirumab and aflibercept, which may be a factor contributing to this observation. However, despite drug differences, the total dose was not a risk factor in the present study.…”
Section: Number Of Patients With Proteinuria N (%) -mentioning
confidence: 97%